(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the knowledge of rabies prevention among pupils at primary school in Tam Thanh commune, Vu Ban district, Nam Dinh province in 2023. Research objects and methods: A cross-sectional was conducted on 292 pupils in grades 3, 4, 5 from September 2023 to October 2023 at primary school in Tam Thanh commune, Vu Ban district, Nam Dinh province. Data gathered using an administration questionnaire, then entered by Epidata 3.0, and analyzed by and SPSS 22.0 programs. Results: The results show that 77.7% of the students knew rabies was caused by rabies virus; 82.7% of them knew the route of rabies enter the body is from dog and cat bites; 86.3% of students answered that one of the prevention methods for dogs/cats is the vaccine. Regarding dog and cat bite prevention, 72.3% of the pupils said that they should not tease dogs and cats; only 59.2% of pupils knew how to provide first aid for wounds. Conclusion: The percentage of students having rabies knowledge was high, but the percentage of students who knew how to prevent catching rabies and first aid is low. Thus, there is a need to improve health communication about knowledge of rabies, and integrate the rabies prevention educational program for pupils at primary schools across Nam Dinh province.